Sobre la palinología de algunas especies endémicas e interesantes de Andalucia Oriental. III - Trigo, M. Mar; Hidalgo, M. Isabel; Garcia, Inmaculada; Bootello, M. Lourdes; Nieto-Caldero, Jose? M.; Cabezudo, Baltasar (Acta Botanica Malacitana, 1990)
.